1998
DOI: 10.3109/10641969809053213
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Existence of Insulin-Mediated Decreased Mean Arterial Pressure and Increased Sympathetic Nerve Activity is not Mediated by the Baroreceptor Reflex and Differentially By Hypoglycemia

Abstract: In this study we measured simultaneously and sequentially the lumbar sympathetic nerve activity (LSNA) or renal sympathetic nerve activity (RSNA), mean arterial pressure (MAP), and heart rate (HR) in response to insulin with co-existing hypoglycemia or with glucose replacement in normal rats. Sinoaortic denervation (SAD) was used to evaluate the influence of the baroreflex. LSNA, RSNA, MAP and HR were determined using an acquisition processor and computer software. Bolus insulin infusion where the blood glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
5
11
0
Order By: Relevance
“…Our new findings are consistent with those in a large number of reports in experimental animals and normal humans showing that an increase in plasma insulin levels causes a nonuniform activation of the sympathetic drive [1][2][3][4][5][6][7][8][9][10][11][12]. For instance, in experimental animals, administration of insulin into the cerebral ventricles or intravenously has been shown to increase sympathetic nerve activity in efferent lumbar nerves without affecting efferent renal or adrenal nerves [6,7]. Similarly in normal humans, acute hyperinsulinaemia with euglycaemic clamp increased the sympathetic drive to the forearm and not to the adrenomedullary region [8].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our new findings are consistent with those in a large number of reports in experimental animals and normal humans showing that an increase in plasma insulin levels causes a nonuniform activation of the sympathetic drive [1][2][3][4][5][6][7][8][9][10][11][12]. For instance, in experimental animals, administration of insulin into the cerebral ventricles or intravenously has been shown to increase sympathetic nerve activity in efferent lumbar nerves without affecting efferent renal or adrenal nerves [6,7]. Similarly in normal humans, acute hyperinsulinaemia with euglycaemic clamp increased the sympathetic drive to the forearm and not to the adrenomedullary region [8].…”
Section: Discussionsupporting
confidence: 91%
“…This has been shown using techniques such as venous plasma catecholamine concentration [2] and total body and forearm norepinephrine spillover [3] as well as by direct neural recordings [4,5]. Experiments involving direct measurement of regional sympathetic nerve activity in animal studies have shown that central and systemic insulinaemia cause preferential stimulation of lumbar but not renal or adrenal regions [6,7]. In normal humans and those with insulin resistance it has also been shown that insulinaemia causes nonuniform regional sympathetic activation, with reports showing an increase in output to the forearm and legs but not to the kidneys [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated increased sympathetic traffic to lumbar and renal (8) and adrenal nerves (9) in response to acute hypoglycemia. Insulin-induced hypoglycemia has also been shown to increase plasma norepinephrine after adrenalectomy, consistent with sym- pathoexcitation and catecholamine release from peripheral nerves (16).…”
Section: Discussionmentioning
confidence: 99%
“…Hoffman et al (7) found that skeletal muscle SNA in type 1 diabetic and nondiabetic human subjects increased during insulin-induced hypoglycemia above that observed during euglycemia at the same insulin infusion rate. Lu et al (8) reported that renal SNA in anesthetized rats exposed to insulinmediated hypoglycemia increased above that observed for hyperinsulinemia with maintained euglycemia. Further, Carlsson et al (9) found that acute insulin-induced hypoglycemia as well as 2-deoxy-D-glucose administration (which induces central neuroglycopenia) increase sympathetic adrenal nerve traffic in anesthetized rats.…”
mentioning
confidence: 99%
“…For instance, the insulin-induced vasodilatation has been reported to be widespread [1, 4], and includes femoral, carotid and coronary vascular beds [5, 6, 7, 8, 9]. The activation of sympathetic output has been found to affect the lumbar region more than adrenal or renal regions [2, 10, 11, 12]. Recently, it has been shown in anesthetized pigs that insulin infusion caused an increase in renal blood flow which was the net result of a vasoconstriction involving sympathetic α-adrenoceptor-mediated mechanisms and a predominant vasodilatation which involved the endothelial release of nitric oxide [13].…”
Section: Introductionmentioning
confidence: 99%